2018
DOI: 10.1096/fj.201701535rr
|View full text |Cite
|
Sign up to set email alerts
|

Deficient transient receptor potential vanilloid type 4 function contributes to compromised [Ca2+] homeostasis in human autosomal‐dominant polycystic kidney disease cells

Abstract: Autosomal-dominant polycystic kidney disease (ADPKD) is a devastating disorder that is characterized by a progressive decline in renal function as a result of the development of fluid-filled cysts. Defective flow-mediated [Ca] responses and disrupted [Ca] homeostasis have been repeatedly associated with cyst progression in ADPKD. We have previously demonstrated that the transient receptor potential vanilloid type 4 (TRPV4) channel is imperative for flow-mediated [Ca] responses in murine distal renal tubule cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…Yamaguchi et al [ 61 ] showed that steady-state [Ca 2+ ] i levels are 20 nM lower in cyst-derived ADPKD cells (57 ± 2 nM) compared with normal human kidney cells (77 ± 2 nM). These findings are similar to the results of Tomilin et al, also obtained in ADPKD [ 62 ]. On the other hand, in ARPKD, using cystic monolayers freshly isolated from PCK rats, Palygin et al demonstrated that basal concentration of Ca 2+ is ∼120 nM, while Zaika et al reported a lower (∼90 nM) level in the same model [ 63 , 64 ].…”
Section: Regulation Of Calcium Handling In Pkd: Polycystins Cilia Calcium Channels Transporters and Purinergic Signaling-dependent Calciusupporting
confidence: 93%
See 1 more Smart Citation
“…Yamaguchi et al [ 61 ] showed that steady-state [Ca 2+ ] i levels are 20 nM lower in cyst-derived ADPKD cells (57 ± 2 nM) compared with normal human kidney cells (77 ± 2 nM). These findings are similar to the results of Tomilin et al, also obtained in ADPKD [ 62 ]. On the other hand, in ARPKD, using cystic monolayers freshly isolated from PCK rats, Palygin et al demonstrated that basal concentration of Ca 2+ is ∼120 nM, while Zaika et al reported a lower (∼90 nM) level in the same model [ 63 , 64 ].…”
Section: Regulation Of Calcium Handling In Pkd: Polycystins Cilia Calcium Channels Transporters and Purinergic Signaling-dependent Calciusupporting
confidence: 93%
“…There is evidence that improper flow-mediated [Ca 2+ ] i responses are involved in both ARPKD and ADPKD cystogenesis [ 37 ], potentially through the effects on the transduction of the flow sensation by the renal cilia, or mechanosensitive properties of the ion channels and transporters themselves. The transient receptor potential vanilloid type 4 (TRPV4) channels could play an important modulatory role in the process of mechanosensation [ 62 , 64 ]. TRPV4 is a Ca 2+ -permeable, nonselective cation channel that can be activated by various chemical, osmotic and mechanical signals.…”
Section: Regulation Of Calcium Handling In Pkd: Polycystins Cilia Calcium Channels Transporters and Purinergic Signaling-dependent Calciumentioning
confidence: 99%
“…Expression and functional activity of several TRP channels, including TRPC3, TRPC6, and TRPV4, have been reported in the native CD cells and CD-derived cultures [16, 17]. Accumulated evidence has demonstrated that TRPV4 is indispensable for flow-induced [Ca 2+ ] i elevations [1719]. However, TRPV4 -/- mice do not demonstrate measurable defects in the renal water handling [20, 21] indicating that distinct molecular mechanisms are involved in sensing changes in flow and osmolarity in the CD.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant cumulative evidence shows that TRPV4 serves as a mechanical sensor of tubular flow in the ASDN [5][6][7][8][9]. TRPV4 dysfunction compromises [Ca 2+ ] i homeostasis and abolishes flow-induced elevations of Cells 2021, 10, 2 of 17 [Ca 2+ ] i in native freshly isolated split-opened ASDN of rodents and in primary cultures of human distal nephron cells [5,10,11].…”
Section: Introductionmentioning
confidence: 99%